Surveilling Surveillance: Countermapping Undocumented Migration in the USA-Mexico Borderlands - Stewart, Haeden Eli; Ostereicher, Ian; Gokee, Cameron; De Leon, Jason (Journal of Contemporary Archaeology, 2017)
This paper examines how mapping technology is central to the operation of the United States Border Patrol security apparatus on the US/Mexico Border, and explores how the very same mapping technology can be used in critique this security project. Drawing on the concept of counter-mapping, we use spatial data collected by the Undocumented Migration Project – a long-term anthropological project aimed at understanding various elements of the violent social process of clandestine migration between Latin America and the United States – to critique the spatial ideology of PTD and the technological conditions of its production.